Aldeia temática: projetos e experiências de etnoturismo entre os Guarani - Gasperazzo, Marcus Vinicius (2017)
Guarani groups living in the north coast of Espirito Santo (Brazil) in a region devastated by agribusiness and the recent implementation of new industrial enterprises, have been rehearsing new proposals for cultural projects and events, investing in the diversification of their activities in the ambit of ethnotourism. In this context, there has been the identification of village spaces as attractive for "exotic" and "alternative" cultural interventions with external investments potentially in favor of the groups, with significant refusals in indigenous visibility assemblages. We suggest drawing a trajectory of these negotiated scenarios, from the creation of a scenographic village to a rave, following the strategies of reappropriation and resignification of these spaces-time by the indigenous people and the tensions and socio-political reordering of the groups, from a perspective Which contemplates, at the same time, the strengthening of the way of being and living Guarani and the redefinition of relations / negotiations with the whites.